Analysis of soil hydraulic and thermal properties for land surface modeling over the Tibetan Plateau - Zhao H. (null, 2020)
Results show that porosity and SHP and STP differ across the climate zones and strongly depend on soil texture. In particular, it is proposed that gravel impact on porosity and SHP and STP are both considered in the arid zone and in deep layers of the semi-arid zone. Parameterization schemes for porosity, SHP and STP are investigated and compared with measurements taken. To determine the SHP, including soil water retention curves (SWRCs) and hydraulic conductivities, the pedotransfer functions (PTFs) developed by Cosby et al. (1984) (for the Clapp–Hornberger model) and the continuous PTFs given by Wösten et al. (1999) (for the Van Genuchten–Mualem model) are recommended.